Synthesis of dual thermoresponsive ABA triblock copolymers by both living cationic vinyl polymerization and RAFT polymerization using a dicarboxylic RAFT agent - Sugihara, Shinji (Elsevier Ltd., 2014)
Link to publisher's homepage at http://www.elsevier.com/